Systematic review of diplommatinid land snails (Caenogastropoda, Diplommatinidae) endemic to the Palau Islands. (1) Generic classification and revision of Hungerfordia species with highly developed axial ribs - Yamazaki, Kazunori; Yamazaki, Midori; Ueshima, Rei (Zootaxa, 2013)
Diplommatinidae is a family of terrestrial caenogastropod snails that shows extensive species diversity and endemic radiation within the Palau (Belau) Islands. In this paper, we revised the taxonomy of Palauan endemic diplommatinids based on the comparative morphology of shell, operculum, radula, and genitalia. Although the generic classification of Palauan diplommatinids has been confusing, they are currently classified into two genera, Hungerfordia Beddome, 1889 and Palaina Semper, 1865. Palauan diplommatinids of these two genera are primarily distinguished by the radular, genital and operculum morphology. However, shell morphology, on which taxonomy has traditionally been based, does not provide definitive characters for generic identification, because shell shape and sculpture are highly variable within each genus. Although Hungerfordia has long been known as a monotypic genus, the current study redefines the endemic genus to include a wider range of species that were formerly placed in Diplommatina or Palaina. Following species are transferred to Hungerfordia: H. alata (Crosse, 1866) comb. nov.; H. lamellata (Crosse, 1866) comb. nov.; H. pyramis (Crosse, 1866) comb. nov.; H. ringens (Crosse, 1866) comb. nov.; H. polymorpha (Crosse, 1866) comb. nov.; H. inflatula (Crosse, 1866) comb. nov.; H. lutea (Beddome, 1889) comb. nov.; H. aurea (Beddome, 1889) comb. nov.; H. gibboni (Beddome, 1889) comb. nov.; H. crassilabris (Beddome, 1889) comb. nov. Pseudopalaina Moellendorff in Kobelt & Moellendorff, 1898 (synonym nov.) is demoted as a junior synonym of Hungerfordia. Palaina is also redefined based on the internal shell features and operculum morphology, in addition to the external shell characters. Furthermore, Eupalaina Kobelt & Moellendorff, 1898 is restored as a subgenus of Palaina for Palauan species on the basis of a genital character. The taxonomy of Hungerfordia species with highly developed axial ribs is revised. H. pelewensis Beddome, 1889, H. lamellata (Crosse, 1866) comb. nov., and H. alata (Crosse, 1866) comb. nov. are redescribed with new morphological data. Following new taxa are described: H. triplochilus sp. nov., H. expansilabris sp. nov., H. nudicollum sp. nov., H. echinata echinata sp. et subsp. nov., H. echinata tubulispina subsp. nov., H. elegantissima sp. nov., H. goniobasis goniobasis sp. et subsp. nov., H. goniobasis dmasechensis subsp. nov., H. subalata sp. nov., H. pteropurpuroides sp. nov., H. papilio papilio sp. et subsp. nov., H. papilio stenoptera subsp. nov..